2020
DOI: 10.1002/ejp.1664
|View full text |Cite
|
Sign up to set email alerts
|

Overactivity assessment in chronic pain: The development and psychometric evaluation of a multifaceted self‐report assessment

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…As part of the medical assessment, a screen for overactivity behaviour is conducted using interview techniques. The questions posed to consumers are similar to those questions presented in the Overactivity in Persistent Pain Assessment (OPPA; Andrews et al, 2021). Consumers identified as displaying overactivity tendencies were provided with activity pacing education by the clinical team as part of their treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of the medical assessment, a screen for overactivity behaviour is conducted using interview techniques. The questions posed to consumers are similar to those questions presented in the Overactivity in Persistent Pain Assessment (OPPA; Andrews et al, 2021). Consumers identified as displaying overactivity tendencies were provided with activity pacing education by the clinical team as part of their treatment.…”
Section: Methodsmentioning
confidence: 99%
“…The OPPA (Andrews et al, 2021) is multifaceted self‐report overactivity measure that assesses habitual overactivity behaviour in the context of chronic pain. The questionnaire assesses five features of overactivity severity including: frequency, severity of the pain exacerbation, impact on occupational performance, recovery time, and maladaptive coping.…”
Section: Methodsmentioning
confidence: 99%
“…Overactivity is one characteristic activity pattern in individuals with CP and indicates the tendency to continue with activities despite pain 2,3 . Individuals with overactivity excessively engage in activities, resulting in additional pain and reduced functional capacity 4 …”
Section: Introductionmentioning
confidence: 99%
“…2,3 Individuals with overactivity excessively engage in activities, resulting in additional pain and reduced functional capacity. 4 Individuals suffering from CP with overactivity also frequently experience sleep disturbance. [5][6][7] A previous study using accelerometers revealed that engagement in high-intensity activities and high fluctuations in activities throughout the day (both characteristics of overactivity) are associated with poorer sleep at night.…”
Section: Introductionmentioning
confidence: 99%
“…Overactivity is one characteristic activity pattern in individuals with CP and means the tendency to continue with activities despite pain [2,3]. Individuals with overactivity excessively engage in activities, resulting in additional pain and reduced functional capacity [4].…”
Section: Introductionmentioning
confidence: 99%